SUPPLEMENTING BOTH MUSCLES AND THE BRAIN: A LITERATURE REVIEW ON THE POTENTIAL OF CREATINE SUPPLEMENTATION IN COGNITIVE PERFORMANCE IN SELECTED DEMOGRAPHIC SUBGROUPS - Alicja Bury; Patryk Biesaga; Konrad Kotte; Olaf Jadanowski; Kamil Łebek; Weronika Sobota; Przemysław Piskorz; Daria Litworska-Sójka; Bartosz Komsta; Julia Lipiec (International Journal of Innovative Technologies in Social Science, 2025)
Creatin is one of the most common supplements for athletes and has been well-studied for its safety and efficiency. It has a documented impact on enhanced performance and recovery among sportsmen. Considering, many researchers have decided to study its impact on cognitive performance in different patient demographics. The positive impact of creatin on cognition observed in studies on athletes sparked interest in its usefulness in different demographic groups. Its favorable price and nearly adverse effect-free profile would make it a great nutraceutical for large-scale use. This study aimed to review the currently published clinical trials on the effect of creatin on cognitive performance in specific subgroups, i.e. healthy adult participants, healthy elderly participants as well as patients suffering from certain psychiatric conditions. The analysis of the published trials showed weak to moderate evidence on creatin’s role in cognitive performance improvement. More large-scale randomized studies are warranted to establish the therapeutic value of creatin supplementation on mental processes.